2022
DOI: 10.3390/s22041633
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Gait Analysis of Patients with Severe Symptomatic Spinal Stenosis Utilizing the Gait Profile Score: An Observational Clinical Study

Abstract: Lumbar spine stenosis (LSS) typically manifests with neurogenic claudication, altering patients’ gait. The use of optoelectronic systems has allowed clinicians to perform 3D quantitative gait analysis to quantify and understand these alterations. Although several authors have presented analysis of spatiotemporal gait parameters, data concerning kinematic parameters is lacking. Fifteen patients with LSS were matched with 15 healthy controls. Quantitative gait analysis utilizing optoelectronic techniques was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Kinematic movement parameter analyses in LST patients have repeatedly shown alterations particularly of lumbar and pelvic movement, with measurable impact of lower limb [ 26 ] and lower back pain [ 37 ] on movement patterns, and with objective and quantifiable measures of improvement after surgical intervention [ 28 , 29 ]. One recent study [ 38 ] using optoelectronic techniques in a specialized laboratory setting described limited internal/external pelvic rotation and craniocaudal movement, limited hip extension and abduction/adduction, as well as limited ankle plantar flexion in this patient group. Our study confirms these previous findings in that the ROM of the hip and ankle were also restricted in our LST patients, while adding the observation of an additionally impaired ROM of the shoulders, which has not been reported before.…”
Section: Discussionmentioning
confidence: 88%
“…Kinematic movement parameter analyses in LST patients have repeatedly shown alterations particularly of lumbar and pelvic movement, with measurable impact of lower limb [ 26 ] and lower back pain [ 37 ] on movement patterns, and with objective and quantifiable measures of improvement after surgical intervention [ 28 , 29 ]. One recent study [ 38 ] using optoelectronic techniques in a specialized laboratory setting described limited internal/external pelvic rotation and craniocaudal movement, limited hip extension and abduction/adduction, as well as limited ankle plantar flexion in this patient group. Our study confirms these previous findings in that the ROM of the hip and ankle were also restricted in our LST patients, while adding the observation of an additionally impaired ROM of the shoulders, which has not been reported before.…”
Section: Discussionmentioning
confidence: 88%
“…The characteristics of gait deterioration in patients with LSS compared to those in healthy subjects include decreased gait velocity (35,38,42,44,46), decreased time or length of gait (step or stride) (21,22,28,32,33,35,38,40,44), decreased cadence (21,22,35,42), gait asymmetry (38), and prolonged gait duration (21,22,32,35,38). Kinematic analysis showed that LSS decreased hip ROM (42), increased knee ROM (42) and lumbar flexion (anterior trunk tilt) in the sagittal plane (44), and increased the foot contact time and progression angle (34).…”
Section: Summary Of Publications On Objective Quantitative Gait Analy...mentioning
confidence: 99%
“…Spatiotemporal gait metrics Decreased gait velocity (21,35,38,42,44,46), decreased time or length of gait (step or stride) (21,22,32,33,35,38,40,44), and decreased cadence (42), prolonged gait duration Kinematic variable Decreased hip and knee range of motion (42) Lumbar flexion (anterior trunk tilt) in the sagittal plane (20,43,44) Kinetic variable Increased knee flexion torques (20) Electromyography Muscle activity in the LSS was higher in the tensor fascia, quadriceps (37), and vastus lateralis muscles (20) and lower in the paravertebral muscles (20). intelligence to provide useful information for healthcare providers regarding treatment.…”
Section: Gait Type Neurogenic Intermittent Claudication Painful Limp ...mentioning
confidence: 99%